A tendência à estabilidade de Fechner na obra de Freud - Mattos, André Santana (2024)
This work consists of an examination of the relationship between the works of Sigmund Freud and Gustav Fechner, based on Fechner’s concept of the tendency to stability, which is incorporated into Freud’s work in 1920, in "Beyond the pleasure principle". The principle of the tendency to stability had been formulated by Fechner in 1873, in the book "Some ideas on the history of creation and development of organisms", having been conceived as a physical principle, according to which every isolated material system would move towards increasingly stable states. This principle would act on organisms, resulting in both the stable cycles of life and the stability of inorganic rest. Freud, in turn, inserts it in his work, taking it as the basis of his principle of constancy, which, along with the pleasure principle, will be understood by him as an expression of the death drive. Adding to this the fact that Fechner understands stability and pleasure as the physical and psychical manifestations of the same process, we have there an interesting and remarkable coincidence between the two authors, who align stability, death and pleasure in their theories. On the other hand, we find an important divergence between the tendency to stability and the principles of regulation of the quantities of excitation, as well as between the conceptions of pleasure of the two authors, where the association explicitly woven by Freud resides. While in Freud a quantitative conception is placed in the foreground, stability and pleasure in Fechner have a more essentially qualitative character. The theme of repetition, which appears in some way in both authors, seems to be even more divergent, as the cyclical repetition characteristic of Fechnerian stability is not represented in the set of phenomena that make up Freud’s repetition compulsion. Even the point of greatest coincidence or theoretical compatibility, however, which is the convergence between tendencies leading to stability, death and pleasure, does not seem to allow for a rigorous theoretical integration, if we consider the specificities of these concepts in each author.